The Legal Analysis Regarding the Overlap of Authorities to Carry Out Seizure in the Problem of Criminal Offenses - Ketut Wisnu Sastrawan; Sagung Putri M.E.Purwani (Interdiciplinary Journal and Hummanity (INJURITY), 2025)
Confiscation has consistently been a contentious issue in legal discourse, particularly concerning the jurisdictional overlap between general confiscation and criminal confiscation. This study employs a normative legal research methodology, utilizing primary and secondary legal materials analyzed through statutory and analytical-conceptual approaches. The research examines the juridical framework of confiscation authority within Indonesian criminal law, specifically addressing corruption cases. The findings reveal that criminal confiscation, grounded in public law principles, takes precedence over general confiscation due to its function in protecting public interests and facilitating criminal investigations. However, this prioritization does not negate the rights protected by general confiscation; rather, criminal confiscation serves evidentiary purposes, after which confiscated assets must be returned to legitimate claimants. The study concludes that Article 39(2) of the Criminal Procedure Code provides legal legitimacy for prioritizing criminal confiscation, while simultaneously requiring investigators to maintain confiscated objects under court supervision rather than direct investigator control. This research contributes to resolving the normative conflict between criminal and civil confiscation procedures, offering practical guidance for law enforcement and judicial authorities.